How E-WOM motivations vary by hotel review website. Issue 8 (13th August 2018) - Belarmino, Amanda Mapel; Koh, Yoon
Abstract : Purpose: Based on equity theory, this paper investigates if guests write on different review websites because of different internal motivations. Furthermore, it examines the moderating effect of service' exceeds, neutral, negative, and service recovery–on the relationship between motivations and type of website to write reviews. Design/methodology/approach: To exam if the star ratings of the same hotels were significantly different across hotel, online travel agency, and third-party review websites, this study collected 12, 000 star ratings from 40 hotels across the US and conducted t-tests. A survey of 1, 600 US travelers was administered to uncover the motivations for writing on different websites/website combinations. Four different scenarios were used to test the moderating effect of service: exceeds, neutral, negative, and service-recovery. These responses were analyzed using backwards stepwise regression. Findings: Star ratings for the same hotel do differ among the three websites; hotel is the highest and third-party is the lowest. There are seven distinct groups of guests. Guests are motivated to write reviews to balance inequitable relationships. They decide which website/website combination best improves the equity relationship. This research indicates that guests' choice of website is based on different internal motivations. The moderating effect of the service experience was significant. Originality/value: This paper contributes to the literature by examining different motivations to write online reviews by website. Prior research typically examined one website or aggregated results from multiple websites, ignoring website specific differences. This can help hoteliers to understand why initiatives to promote reviews on certain websites may be unsuccessful.